COMPARISON OF NOUNS IN RUSSIAN AND ENGLISH LANGUAGES (THESIS) - Aliyeva Dilbar Valiyevna (Лучшие интеллектуальные исследования, 2024)
Russian nouns and English nouns have several notable differences. Firstly, Russian nouns are categorized into three grammatical genders (masculine, feminine, and neuter), each of which impacts the forms of associated adjectives and verbs. In contrast, English nouns don't have grammatical gender. Additionally, Russian nouns decline to reflect case (nominative, genitive, dative, accusative, instrumental, and prepositional), affecting their role in a sentence, while English nouns generally have a fixed form, with case distinctions primarily limited to pronouns. English nouns rely more heavily on word order for sentence structure, whereas Russian nouns' endings and cases play a more pivotal role in conveying meaning and relationships within a sentence.